Psychiatric comorbidities in neurodevelopmental disorders - King, Bryan H (Current opinion in neurology, 2016)
Recent changes in the diagnostic criteria for psychiatric and neurodevelopmental disorders as well as increases in the prevalence of both have elevated the focus on these areas of medicine and their clinical overlap. Several recent studies have examined psychiatric comorbidities in neurodevelopmental disorders including autism and specific genetic syndromes. A growing number of reports underscore the genetic overlap between previously distinct clinical disorders. Behavioral and psychiatric features are increasingly identified in association with intellectual developmental disorders. As there have been advances in our collective understanding of the genetic underpinnings of certain disorders and the downstream physiological consequences of those genetic alterations, challenges to the way boundaries have been drawn around psychiatric disorders, and by extension, the concept of comorbidity, warrant review.